Calidad de la educación, producción de conocimiento y crecimiento endógeno. (1997)
Versatility, creativity and the ability to socialize knowledge are intellectual atributes that may be seen as observable outputs of specific cognitive structures. These structures develop in learning processes,, through spontaneous, educational and institutional processes that provide experience and social incentives to individuals.